Bruton tyrosine kinase is a therapeutic target in stem-like cells from multiple myeloma - Yang, Ye (Cancer Res, 2015)
Ibrutinib (Imbruvica®), a small-drug inhibitor of Bruton tyrosine kinase (BTK), is currently undergoing clinical testing in patients with multiple myeloma (MM), yet important questions on the role of BTK in myeloma biology and treatment are outstanding. Using flow-sorted side population (SP) cells from human myeloma cell lines (HMCLs) and MM primary samples as surrogate fort the elusive multiple myeloma stem cell (MMSC), we found that elevated expression of BTK in myeloma cells leads to AKT/WNT/β-catenin-dependent up-regulation of key stemness genes (OCT4, SOX2, NANOG, MYC) and enhanced self-renewal. Enforced transgenic expression of BTK in myeloma cells increased features of cancer stemness, including clonogenicity and resistance to widely used myeloma drugs, whereas inducible knockdown of BTK abolished them. Furthermore, over-expression of BTK in myeloma cells promoted tumor growth in laboratory mice and rendered SP-derived tumors that contained high levels of BTK more sensitive to the selective, second-generation BTK inhibitor, CGI1746, than SP-derived tumors that harbored low levels of BTK. Taken together, these findings implicate BTK as a positive regulator of myeloma stemness and provide additional support for the clinical testing of BTK-targeted therapies in patients with myeloma.